Seroprevalence and molecular detection of Toxoplasma gondii in healthy blood donors in southwest Iran. (February 2019) - Saki, J.; Foroutan, M.; Khodkar, I.; Khodadadi, A.; Nazari, L.
Abstract: Background: Toxoplasmosis is a cosmopolitan parasitic disease caused by Toxoplasma gondii ( T. gondii ). Blood transfusion is a probable route of T. gondii transmission. Due to lack of information about seroprevalence of T. gondii in healthy blood donors, this study was aimed to determine the chronic and acute infection using serological and molecular methods. Material and methods: In this cross-sectional investigation, 380 samples were collected from donated bloods. Anti- Toxoplasma IgG and IgM antibodies were examined using enzyme-linked immunosorbent assay (ELISA). Also, all IgG positive samples were tested by IgG avidity test. Eventually, to detection of active infection, DNA was extracted from IgM positive and low IgG avidity samples and then tested using nested-polymerase chain reaction (PCR). Results: Among 380 blood donors, 131 (34.47%) were positive for only anti- T. gondii IgG, 2 (0.5%) were positive for only anti- T. gondii IgM, and 11 (2.9%) were positive for both IgG and IgM antibodies. Then, 142 samples (131 IgG + and 11 IgG + IgM + ) were evaluated using IgG avidity test. Of these, 115 (81%) had high avidity IgG indicates past infection; 16 (11.26%) had low avidity IgG representing recent infection, and 11 (7.74%) were equivocal. With nested PCR, 20 samples of 50 seropositive samples were diagnosed positive. Conclusion: Detected active infection using nested-PCR draws attention to the possibility of T. gondii infection via blood transfusion which emphasizes the importance of parasite DNA screening before donation of blood in high risk groups such as: multi-transfused persons, immunosuppressed patient, and pregnant women.